Assessing trophic interactions among three tuna species in the Solomon Islands based on stomach contents and stable isotopes - Jiang, Ri Jin; Yang, Fan; Chen, Feng; Yin, Rui; Liu, Ming Zhi; Zhu, Wen Bin; Guo, Ai; Liu, Lian Wei (Frontiers in Marine Science, 2022)
Nutrition research is essential to the conservation and management of fishery resources. This study analyzed the feeding habits and nutritional interactions among three tuna species in the waters of the Solomon Islands (5°12′S–15°20′S, 157°31′E–172°19′E). A total of 120 bigeye tuna (Thunnus obesus), 353 yellowfin tuna (Thunnus albacores), and 307 albacore tuna (Thunnus alalunga) samples were collected from September to December 2019 for gastric content and stable isotope analysis. The results showed that the stomach contents of the three tuna species were rich in prey, and 49 prey species were identified, including fish, cephalopods, and crustaceans, with high phenotypic components (BPC). Yellowfin tuna consumed the largest variety of food and bigeye tuna consumed the smallest. The feeding intensity and nutritional grade of bigeye tuna were higher than those of yellowfin and albacore tuna. Yellowfin tuna had the highest empty stomach rate and lowest average gastric fullness index. The degree of stomach fullness in the three tuna species was mainly 1, and the difference in the stomach fullness index among them was significant (P<0.001). Food overlap (0.3–0.6) and Levins index (<0.6) among the three species were low, indicating a specialized feeding tendency. The δ13C and δ15N values of the three tuna species were significant (P<0.001). The SEAc (the standard ellipse area corrected for small sample sizes) and TA (total niche area) of bigeye tuna, NR (range of δ15N) of yellowfin tuna, and CR (range of δ13C) of albacore tuna were the highest. The results of this study will help improve our understanding of the feeding ecology of these three tuna species and their important roles in the ecosystem and food web structure.